Rhyming ethics and epic: Journalistic ethics for Chilean students after the pandemics - Lagos Lira, Claudia Paola; Chávez Bravo, Cristóbal (Re-presentaciones: Periodismo, comunicación y sociedad, 2025)
This essay analyzes the classroom adjusting experience of a mandatory course on journalistic ethics taught to college-level students at the University of Chile, the country’s largest public university. This experience was developed at the beginning of the second decade of the 21st century, in the aftermath of COVID-19 pandemic, and a social uprising as a sociopolitical context. We systematized a collaborative endeavor over a five-years period, and discuss it in light of the literature on university-level models for teaching journalistic ethics in diverse contexts, under different theoretical and epistemic frames, strategies and practices, highlighting the particularities of this case study situated within a specific higher education system, journalistic field and culture of the Global South.